2014
DOI: 10.1063/1.4865236
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties and large magnetocaloric effects in bonded La(Fe, Si)13-based magnetic refrigeration materials

Abstract: Bonded La(Fe, Si)13 magnetic refrigeration materials have been prepared, and the microstructure, mechanical properties, and magnetocaloric effect (MCE) of bonded LaFe11.7Si1.3C0.2Hx have been investigated systematically. Bonded materials show porous architecture, and the mechanical properties increase with the increase of epoxy resin content, which could fill more pores and boundaries and thus enhance the binding force between different particles. Bonded LaFe11.7Si1.3C0.2H1.8 with 3 wt. % epoxy resin exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Considering that powder cannot measure compressive strength, we used a bulk mother sample in this work. The maximum compressive strength of bulk LaFe 11.6 Si 1.4 alloy is 155 MPa, which is in good agreement with previously reported values for La(Fe,Si) 13 alloys [27,28]. The maximum values of the compressive strength for Bi powder bonded samples containing 5, 10, and 15 wt % are as high as 263, 306, and 358 MPa, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Considering that powder cannot measure compressive strength, we used a bulk mother sample in this work. The maximum compressive strength of bulk LaFe 11.6 Si 1.4 alloy is 155 MPa, which is in good agreement with previously reported values for La(Fe,Si) 13 alloys [27,28]. The maximum values of the compressive strength for Bi powder bonded samples containing 5, 10, and 15 wt % are as high as 263, 306, and 358 MPa, respectively.…”
Section: Resultssupporting
confidence: 90%
“…33,34,35,36 This has resulted in a shift of focus towards material systems that lie closer to the critical point: on the cusp of first order and continuous phase transitions. As this technology approaches maturity it is reasonable to speculate that focus will continue to shift towards tri-critical magnets that can be easily shaped, react well with thermal engineering, and respond rapidly to changing magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…In the fourth method it was reported that the nearly single NaZn 13 -type phase could be obtained when LaFe 10.8 Co 0.7 Si l.5 C 0.2 powders were sintered at 1100℃ for 4h with 25 LaFe 0.9 Co 0.27 Si 1.17 as a sintering aid, and very few La-rich impurity phase was present [20]. Recently, epoxy-bonded bulk/plate La(Fe,Si) 13 -based compounds were presented by Zhang [21] and Pulko [22], the results show that the epoxy-bonded composite is a promising solution for the manufacturing of more efficient active magnetic regeneration (AMR) with better mechanical properties compared to sintered AMR. However, the magnetocaloric and thermal performances of the epoxy-bonded plates are substantially lower compared to the sintered plates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%